Green Hydrothermal Synthesis of Fluorescent 2, 3‐Diarylquinoxalines and Large‐Scale Computational Comparison to Existing Alternatives. Issue 8 (14th April 2021) - Amaya‐García, Fabián; Caldera, Michael; Koren, Anna; Kubicek, Stefan; Menche, Jörg; Unterlass, Miriam M.
Abstract: Invited for this month′s cover is the group of Miriam Unterlass at the Technische Universität Wien and the CeMM Research Center for Molecular Medicine of the Austrian Academy of Sciences. The image illustrates the synthesis of quinoxalines in "hot water" and the large‐scale computational comparison of all existing syntheses of these quinoxalines. The Full Paper itself is available at 10.1002/cssc.202100433 . Abstract : "We love hydrothermal synthesis…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202100433 . View the Front Cover here: 10.1002/cssc.202100608 .